Jihadism and crime in Spain: a convergence settings approach - Argomaniz, Javier (European journal of criminology, 2019)
This article explores the melting pot of jihadists and criminals that has featured in some of the most significant jihadist attacks and plots foiled in Spain over the last 15 years. Applying Felson’s offender convergence settings theory to this case, we argue that the confluence of criminality and jihadism observed in other European contexts has also been present in the Spanish case. Individuals with criminal pasts have utilized their skills for terrorist attacks, a variety of forms of crime have been used to fund terrorism, and certain settings such as prisons have facilitated the convergence between criminals and jihadists and enabled a process of identity transition.